Lake hydrology, water quality and ecology impacts of altered river–lake interactions: advances in research on the middle Yangtze river - Guishan Yang; Qi Zhang; Rongrong Wan; Xijun Lai; Xia Jiang; Ling Li; Huichao Dai; Guangchun Lei; Jianchi Chen; Yongjun Lu (Hydrology Research, 2016)
Water and mass exchange between rivers and lakes are key processes that maintain the health of the ecology of river–lake systems. Alteration to river–lake interactions have great impacts on water and mass balances. Naturally connected to the middle Yangtze River are the Poyang Lake and Dongting Lake, which are the largest and the second largest freshwater lakes in China. The operation of the Three Gorges Dam (TGD) in the upper Yangtze River was found to have substantial impacts on the middle Yangtze river–lake system. In the past decade, unusual seasonal dryness was evident in the two lakes. Considerable deviations in lake water quality and wetland ecosystem were also detected. In order to explore and distinguish the causal factors influencing the river–lake system, the Ministry of Sciences and Technology (China) launched a research project in 2012, the National Basic Research Program of China (973 Program) (2012CB417000). This article provides an overview of advances in this research, including the evolution of the river–lake interactions, the impacts of the TGD, and the influences on lake hydrology, water quality, and ecosystem. The 20 papers in this issue deliver part of the research outcomes of this project.